2010
DOI: 10.1016/j.tins.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and plasticity

Abstract: As any new parent knows, having a baby provides opportunities for enrichment, learning and stress -experiences known to change the adult brain. Yet surprisingly little is known about the effects of maternal experience, and even less about the effects of paternal experience, on neural circuitry not directly involved in parenting. Here we discuss how caregiving and the accompanying experiential and hormonal changes influence the hippocampus and prefrontal cortex, brain regions involved in cognition and mood regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 115 publications
1
109
0
1
Order By: Relevance
“…Sire behaviour was qualitatively similar to maternal behaviour but was less efficient in that male response levels were slower and less frequent. The 50–60% of sires that showed parental behaviour in this study is similar to the proportion reported in other rodents246781727.…”
Section: Discussionsupporting
confidence: 88%
“…Sire behaviour was qualitatively similar to maternal behaviour but was less efficient in that male response levels were slower and less frequent. The 50–60% of sires that showed parental behaviour in this study is similar to the proportion reported in other rodents246781727.…”
Section: Discussionsupporting
confidence: 88%
“…43–45 Nurses’ support of mothers’ efforts to protect themselves and their offspring 46 is likely to buffer the damaging effects of toxic stress on mothers’ rapidly changing neural circuitry and behavior during pregnancy and the puerperium. 43–48 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, in utero exposure to stress or to a variety of pharmacological agents almost invariably reduces neurogenesis in adulthood (Korosi et al 2012). Postnatal exposure to stress yields more variable results, and is modified by maternal and paternal factors, sex, genetic background, and epigenetic changes, although suppression of neurogenesis prevails here as well (Leuner et al 2010;Lucassen et al 2010aLucassen et al ,b, 2013bKoehl et al 2012;Loi et al 2014). Neuronal survival was decreased and apoptosis was increased in offspring of lowcaring mothers versus offspring of high-caring mothers (Weaver et al 2002;Bredy et al 2003).…”
Section: Long-lasting Effects Of Perinatal Stress Exposurementioning
confidence: 99%